Association between food-derived water intake and oral health indicators among Korean older adults living alone: a cross-sectional study using data from the 2020–2024 Korea National Health and Nutrition Examination Survey - Ji-Young Lee; Da-Jeong Kim; Yu-Rin Kim (Journal of Korean Society of Dental Hygiene, 2026)
Objectives: To compare food-derived water intake and oral health between Korean older adults living in single-person households (SG) and those living in multi-person households (MG), and to examine the association between food-derived water intake and oral health among those living alone using data from the 2020–2024 Korea National Health and Nutrition Examination Survey (KNHANES). Methods: This cross-sectional study included 8,164 adults aged ≥65 years (SG=2,158; MG=6,006). Food-derived water intake was categorized into quartiles (Q1-Q4). Oral health indicators included the number of natural teeth and self-reported difficulties with chewing and speaking. Complex sample analyses were performed after adjustment for sociodemographic characteristics and comorbidities. Results: Participants in SG had lower food-derived water intake than those in MG, with Q1 being the most common in SG (25.1%) and Q4 in MG (32.2%) (p